Pendekatan Hermeneutik dalam Pengkajian Hadis: Analisis Pemaknaan Hadis Tentang Peran Perempuan di Ranah Publik - Winda Islamitha Nurhamidah; Nur Azizatul Haqiah; Lutfiah Holifa Balkis; Amri Saputra; Ahmad Arifi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the interpretation of hadiths concerning women’s roles in the public sphere through a hermeneutical approach, reaffirming an inclusive and contextual Islamic perspective on gender. The research arises from the dominance of literal and patriarchal readings of hadiths that tend to limit women’s participation in social and educational domains. Employing a qualitative library research method, this study examines relevant hadith texts and explores the views of contemporary Muslim hermeneutical thinkers such as Nasr Hamid Abu Zayd, Fazlur Rahman, and Amina Wadud. The findings reveal that hermeneutics provides a methodological framework capable of fostering gender-just interpretations by emphasizing the historical, social, and moral dimensions of the hadith text. The reinterpretation demonstrates that many hadiths previously understood restrictively are, in fact, contextual rather than universally normative. The study’s implications encourage a new paradigm in Islamic scholarship that is more reflective, critical, and socially responsive. The novelty of this research lies in integrating hermeneutical analysis with thematic hadith studies on women’s participation in the public domain, an area rarely explored in depth. This research thus contributes significantly to developing a more humanistic and egalitarian Islamic epistemology.